2020
DOI: 10.1177/1937586720972078
|View full text |Cite
|
Sign up to set email alerts
|

Lighting the Patient Room of the Future: Evaluating Different Lighting Conditions for Performing Typical Nursing Tasks

Abstract: Purpose: This study explores how aspects of lighting in patient rooms are experienced and evaluated by nurses while performing simulated work under various lighting conditions. The lighting conditions studied represent design standards consistent with different environments of care—traditional, contemporary, and future. Background: Recent advances in lighting research and technology create opportunities to use lighting in hospital rooms to improve everyday experience and provide researchers with opportunities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
1
15
0
3
Order By: Relevance
“…Condition 6 represents a typical midday condition. Table 3 shows the MI and CS values for each of these lighting conditions; the full SPD data for the calculations were provided in an earlier paper (Graves et al, 2021). The relative SPDs are shown graphically in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Condition 6 represents a typical midday condition. Table 3 shows the MI and CS values for each of these lighting conditions; the full SPD data for the calculations were provided in an earlier paper (Graves et al, 2021). The relative SPDs are shown graphically in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…This sample size was determined based on expectations that it would provide sufficient power for the types of statistical analyses planned to evaluate the participants’ results. Uttley (2019) showed that samples of 25–35 subjects provide sufficient statistical power to detect most large and medium effects in within-subjects experimental research, and in the prior experiment conducted by this team, significant differences in perceptions of the participants were successfully revealed with 33 subjects (Graves et al, 2021).…”
Section: Methodmentioning
confidence: 96%
See 3 more Smart Citations